2009
DOI: 10.1038/jcbfm.2009.55
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Dynamics of Subventricular Zone Neuroblast Migration in the Ischemic Striatum of the Adult Mouse

Abstract: The migratory behavior of neuroblasts after a stroke is poorly understood. Using time-lapse microscopy, we imaged migration of neuroblasts and cerebral vessels in living brain slices of adult doublecortin (DCX, a marker of neuroblasts) enhanced green fluorescent protein (eGFP) transgenic mice that were subjected to 7 days of stroke. Our results show that neuroblasts originating in the subventricular zone (SVZ) of adult mouse brain laterally migrated in chains or individually to reach the ischemic striatum. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 46 publications
7
105
1
3
Order By: Relevance
“…25,33 Studies in rodent models of stroke have shown the proliferation and migration of new neurons that appear to travel to the injured striatum and cortex within 24 hours and up to 6 weeks after injury. 5,36,48,77 In one report, stroke in adult mice caused neuroblasts to migrate in chains from the SVZ to the striatum at an average speed of 28.67 μm/hr. 77 Several TBI studies using a cortical impact injury model in mice and rats have demonstrated new neurons near the focal site of injury from 3 days to 3 weeks postinjury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,33 Studies in rodent models of stroke have shown the proliferation and migration of new neurons that appear to travel to the injured striatum and cortex within 24 hours and up to 6 weeks after injury. 5,36,48,77 In one report, stroke in adult mice caused neuroblasts to migrate in chains from the SVZ to the striatum at an average speed of 28.67 μm/hr. 77 Several TBI studies using a cortical impact injury model in mice and rats have demonstrated new neurons near the focal site of injury from 3 days to 3 weeks postinjury.…”
Section: Discussionmentioning
confidence: 99%
“…5,36,48,77 In one report, stroke in adult mice caused neuroblasts to migrate in chains from the SVZ to the striatum at an average speed of 28.67 μm/hr. 77 Several TBI studies using a cortical impact injury model in mice and rats have demonstrated new neurons near the focal site of injury from 3 days to 3 weeks postinjury. 7,66,70 Indeed, Covey et al 13 showed that the critical period for neocortical neurogenesis in postnatal Day 6 mice was between 4 and 7 days after cryoinjury.…”
Section: Discussionmentioning
confidence: 99%
“…70,84 Also like the cells in the SGL, those NPCs that do survive migrate out of the SVZ into the striatum and neocortex and mature into functional neurons. 73,[85][86][87][88][89] In addition, it has been demonstrated that transient angiogenesis after stroke allows neuroblasts to migrate along these newly formed blood vessels aiding in their migration out of the SVZ. 89 While some of these newly generated neurons survive up to 5 weeks after ischemia, the majority seem to die with only B0.2% of the cells surviving.…”
Section: Effect Of Ischemia On Neurogenesismentioning
confidence: 99%
“…Dividing neuroblasts undergo tangential migration in the RMS, and then radial migration up into the OB, where they differentiate into two groups of functional interneurons: granule cells (GCs) and juxtaglomerular neurons (JGNs) [3][4][5][6][7][8][9][10]. Whereas the dynamics of SVZ cell migration as well as the tangential migration of neuroblasts in, and their detachment from the RMS, have been studied in much detail [10][11][12][13][14][15][16], little is known about their migratory behavior within the OB.…”
Section: Introductionmentioning
confidence: 99%